TEACHING WRITING BY USING COW (COLLECT, ORGANIZE, WRITING) STRATEGY TO ENHANCE STUDENTSâ WRITING SKILL - Yanpitherszon, Liunokas (Institut Agama Islam Negeri Palopo, 2016)
This research is aimed at finding out the effectiveness of COW (collect, Organize, writing) Strategy effective to enhance studentâs writing ability.Â This research used Pre-Experimental Research and it was conducted in ten meetings. The population of this research is the second year of SMPN. In determining the sample, the researcher used random sampling by taking fifteen students each class. The instruments were used in collecting the data through writing test. And then in calculating the data, the researcher used SPSS Program version 20. The findings of this research show that the use of COW (collect, Organize, writing) Strategy is effective in developing studentsâ writing skill at the second year students of SMAN 1 Soe Kabupaten Timur Tengah Selatan (TTS) NTT.Â It was proven by there was a significant difference between the studentsâ mean score of pretest and posttest. In pretest, the studentsâ mean score is 26 and the studentsâ score in posttest is 51. In addition, the result of statistical analysis for level of significance (p=0.05) with degree of freedom (df)= N-1, where (N) = 25, df = 24. The probability value was smaller than Î± (0.00<0.05). it indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected.